The Role of Combatives Teaching in Physical Education, by Michal Vit and Zdenko Reguli (Revista de Artes Marciales Asiáticas, 2016)
Vit, M., & Reguli, Z. (2015). The Role of Combatives Teaching in Physical Education. Brno: Masaryk University. 128 pp. Retrieved from https://munispace.muni.cz/index.php/munispace/catalog/book/694There is here a new book, dedicated to the application of martial arts elements in physical education. Sequentially are presented authors, the definition of 'combatives', discussed the contents of the book, pointing out its strengths and weaknesses. A short conclusion is finishing the review article.